2014
DOI: 10.7314/apjcp.2014.15.7.3081
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Quality of Life in Turkish Patients with Gynecologic Cancer

Abstract: The aim of this study was to determine the level of social support and quality of life in Turkish patients with gynecologic cancer using a cross-sectional survey design. A total of 108 patients admitted to the gynecologic oncology clinic at a university hospital from September 2011 to January 2012 were included. Data were collected using patient information forms, the Multidimensional Scale of Perceived Social Support (MSPSS) and The Quality of Life-Cancer Survivors Instrument (QOL-CS). Average age was 54.5±10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…5 Age, lower education level negatively affects the QOL but higher education level, employment status, marital status, social support affect positively on QOL. [5][6] The patient with early cervical cancer shows better QOL than with advanced cervical cancer⁷. Treatment modality also affects the QOL, Women who receive combined treatment of cervical cancer by surgery and radiotherapy suffers from urinary incontinence which limit the patient activity, comfort and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…5 Age, lower education level negatively affects the QOL but higher education level, employment status, marital status, social support affect positively on QOL. [5][6] The patient with early cervical cancer shows better QOL than with advanced cervical cancer⁷. Treatment modality also affects the QOL, Women who receive combined treatment of cervical cancer by surgery and radiotherapy suffers from urinary incontinence which limit the patient activity, comfort and quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of cancer causes significant emotional distress for patients and their families (Banning et al, 2010;Carlson et al, 2004;Mystakidou et al, 2004) and some studies showed that cancer patients are at risk of suicide (Lee et al, 2014) and experiencing anxiety and depression (Tuncer et al, 2014) and they had impaired function in many aspects of their life (Nazik et al, 2014). So, the disclosure of cancer-related information to patients can be particularly challenging for health care professionals (Mystakidou et al, 2004;Clayton et al, 2005;Franssen et al, 2009;Kazdaglis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…7 In addition, other studies conducted in Indonesia, Slovakia, Turkey and China show that the quality of life of cancer patients is influenced by family support. [8][9][10][11] The studies related to the quality of life of patients with cervical cancer that have been carried out in Indonesia use more qualitative and quantitative methods with descriptive designs. 3,4,8 In qualitative studies, factors that affect quality of life can be explored but the magnitude of their contribution to quality of life cannot be measured.…”
Section: Introductionmentioning
confidence: 99%